Prevention and management of common musculoskeletal injuries in the adult female athlete - Zumwalt, M. (The active female. Health issues throughout the lifespan, 2023)
As the young female athlete transitions from the adolescent stage into a full-grown adult, her entire body again undergoes a multitude of changes, primarily from the effects of estrogen. This sex-specific hormone causes changes in body composition, muscular strength, neuromuscular firing, and bone content. This bodily alteration opens the adult female athlete up to face different types of musculoskeletal injuries, with overuse trauma such as strains/sprains still being the most common. However, injury to the knee in general and anterior cruciate ligament (ACL) in particular is more of an issue for adult female athletes, with ACL tear rates exceeding that of male athletes several folds, especially for those females participating in soccer and basketball. Current research continues to focus on ACL injury in active females, looking at a wide array of potential contributing factors, both intrinsic and extrinsic, some of which can be modified to aid in preventing further injuries. Prevention of musculoskeletal trauma thus remains the focus and is crucial in keeping the female athlete healthy/injury-free, by incorporating proper training regimens/conditioning programs to help reduce the risk of traumatic injuries.